Studi Kasus PT. Malindo Feedmill, Tbk: Pengaruh Antara Work Environment, Organizational Culture, Extrinsic Motivation, dan Interinsic Motivation yang di Mediasi oleh Employee Engagement terhadap Employee Performance - Marvhieno Ardhian Dumalang; Justine Tanuwijaya (Universitas Batanghari, 2023)
In estimating the exhibition of workers in an organization, it is important to have distinct variable pointers to show whether each instrument shaped has a critical impact. The impact brought about by the worker commitment variable as a middle person on the representative execution variable is the objective of the review. The object of exploration is the administrative center representative of PT. Malindo Feedmill TBK upwards of 79 individuals out of a complete populace of 349 individuals. The examination strategy utilized is the aftereffect of estimations from the savvy PLS 3 application and dependability and legitimacy tests are likewise done with a similar application. Of the six existing speculations, the examination results show that there are three theories that don't uphold, specifically the workplace variable on worker commitment, hierarchical culture on representative commitment, and the keep going is inherent inspiration on worker commitment